The relationship between workplace support and nurses job satisfaction at Ramsay Sime Darby Healthcare, Ara Damansara, Malaysia / Fatin Nabila Mohd Ridzuan - Mohd Ridzuan, Fatin Nabila (Faculty of Business and Management, 2016)
This research paper was conducted to identify the relationship between job satisfaction and workplace support at Ramsay Sime Darby Healthcare, Ara Damansara, Selangor amongst nurses. The population of this study consists of 180 nurses and the sample size were 123 nurses. The sample was obtained using the convenience sampling technique, in which gathering of information from fellows of the population in the organizations who are conveniently to obtain it. The workplace support was represented by four elements; perceived organizational support (POS), supervisor support, co-worker support and mentoring. The findings indicate that generally most of the respondents have a high level of job satisfaction and highly satisfied towards their job. The results of Pearson correlation also revealed that relationship between the workplace support and job satisfaction has strong association with job satisfaction. However, the result on supervisor support has the strongest association on job satisfaction (r=0.839, p=0.000). Still, efforts should be made to improve the existing workplace support in Private Healthcare Providers as it can lead to higher job satisfaction and higher productivity level among the academics staffs. Besides that, the sample of this study was focusing to the nurses. Meanwhile, front liners clinical staffs and doctors are excluded in this study. For future study, it is recommended that the researcher should aim for the different group of professions. Therefore, it could help the researcher to get more diverse and reliable findings.